2011
DOI: 10.1016/j.foodchem.2010.10.049
|View full text |Cite
|
Sign up to set email alerts
|

Red notoginseng: Higher ginsenoside content and stronger anticancer potential than Asian and American ginseng

Abstract: A systematic comparison of the ginsenosides and anticancer activities was performed among white (air-dried) and red (steamed) roots of notoginseng (NG, Panax notoginseng), Asian ginseng (AG, P. ginseng), and American ginseng (AmG, P. quinquefolius). Chemical profiles of different ginseng species were characterized, through simultaneous quantification of nineteen major ginsenosides, by HPLC-UV at 202 nm. The antiproliferative and pro-apoptotic effects on human colorectal cancer cells were determined by MTS meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
97
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(106 citation statements)
references
References 20 publications
(30 reference statements)
8
97
1
Order By: Relevance
“…Ginsenosides extracts were filtrated through 0.22 mm filter into sample loading vial, determined by HPLC based on apparatus and chromatographic conditions of Sun et al (2011) with slight modifications. Chromatographic analyses were performed using an Agilent HPLC instrument (Agilent, Wilmington, U.S.A.) with a quaternary pump, an automatic injector and UV-DAD detector.…”
Section: Quantification Of Ginsenosides By Hplcmentioning
confidence: 99%
“…Ginsenosides extracts were filtrated through 0.22 mm filter into sample loading vial, determined by HPLC based on apparatus and chromatographic conditions of Sun et al (2011) with slight modifications. Chromatographic analyses were performed using an Agilent HPLC instrument (Agilent, Wilmington, U.S.A.) with a quaternary pump, an automatic injector and UV-DAD detector.…”
Section: Quantification Of Ginsenosides By Hplcmentioning
confidence: 99%
“…Red ginseng has been extensively studied and used to improve the condition of a variety of human diseases, and some previous studies have demonstrated that red ginseng has anticancer activity in many types of human malignant cancers [12], [13], [14], [15], [16], [17]. In addition, several other studies have suggested that red ginseng has superior anticancer activities compared to white ginseng [18], [19].…”
Section: Introductionmentioning
confidence: 99%
“…The administration of medication or alteration of diet to prevent or delay the development of cancer is coined “chemoprevention” and has recently drawn public attention due to the low cure rates of advanced lung cancer using traditional approaches, such as chemotherapy and surgery (213). …”
Section: Introductionmentioning
confidence: 99%